Expand or better manage protected areas: A framework for minimizing extinction risk when threats are concentrated near edges - Brendan G. Dillon; Hugh P. Possingham; Matthew H. Holden (Biological Conservation, 2025)

Soft Range Limits Shape Sensitivity to Forest Cover More Strongly Than Hard Range Limits - Natasha R. Granville; Alex L. Pigot; Benjamin Howes; Luiz dos Anjos; Victor Arroyo‐Rodriguez; Luc Barbaro; Jos Barlow; Matthew G. Betts; Alexis Cerezo; Pedro F. Develey; Jack H. Hatfield; Hervé Jactel; et al. (Global Ecology and Biogeography, 2025)
Aim Land‐use change is a major threat to biodiversity, yet there remains considerable unexplained variation in how it affects different populations of the same species. Here, we examine how sensitivity to forest cover changes depending on proximity to different limits of a species' range. By comparing responses as species approach their coastal (‘hard’) and inland (‘soft’) range limits, we aim to provide insight into the relative influence of mass effects, as compared to abiotic and biotic environmental suitability in shaping population sensitivity. Location Global. Time Period 1996–2019. Major Taxa Studied Birds. Methods We combined data from several large databases to obtain a dataset of 2543 bird species surveyed across 116 studies, spanning six continents. Using expert‐verified range maps, we calculated the position of populations relative to their species' nearest inland (‘soft’) and coastal (‘hard’) range limits and categorised the inland limits as equatorward‐ or poleward‐ facing. We investigated how distance to range limits and forest cover, derived from a 30 m‐resolution global dataset, affect the probability of species' incidence. Results We found that bird populations are more sensitive to forest cover when located closer to their species' inland (‘soft’) range limits, whereas this was not the case at coastal (‘hard’) range limits. The heightened sensitivity to forest cover at soft range limits was similar regardless of whether the range limit faced equatorward or poleward. Main Conclusions These results highlight how populations close to the soft limits of their species' ranges are at higher risk of extirpation resulting from loss of forest cover. This suggests that environmental conditions (e.g., climate), which become more challenging away from the core of the species' range, drive variability in sensitivity to forest cover.

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Beyond ecology: ecosystem restoration as a process for social-ecological transformation - Anazélia M. Tedesco; Sofía López-Cubillos; Robin Chazdon; Jonathan R. Rhodes; Carla L. Archibald; Katharina-Victoria Pérez-Hämmerle; Pedro H.S. Brancalion; Kerrie A. Wilson; Mariana Oliveira; Diego F. Correa; Liz Ota; Tiffany H. Morrison; et al. (Trends in Ecology & Evolution, 2023)

Protected area planning to conserve biodiversity in an uncertain future - Richard Schuster; Rachel Buxton; Jeffrey O. Hanson; Allison D. Binley; Jeremy Pittman; Vivitskaia Tulloch; Frank A. La Sorte; Patrick R. Roehrdanz; Peter H. Verburg; Amanda D. Rodewald; Scott Wilson; Hugh P. Possingham; et al. (Conservation Biology, 2023)
Protected areas are a key instrument for conservation. Despite this, they are vulnerable to risks associated with weak governance, land‐use intensification, and climate change. We used a novel hierarchical optimization approach to identify priority areas for expanding the global protected area system that explicitly accounted for such risks while maximizing protection of all known terrestrial vertebrate species. To incorporate risk categories, we built on the minimum set problem, where the objective is to reach species distribution protection targets while accounting for 1 constraint, such as land cost or area. We expanded this approach to include multiple objectives accounting for risk in the problem formulation by treating each risk layer as a separate objective in the problem formulation. Reducing exposure to these risks required expanding the area of the global protected area system by 1.6% while still meeting conservation targets. Incorporating risks from weak governance drove the greatest changes in spatial priorities for protection, and incorporating risks from climate change required the largest increase (2.52%) in global protected area. Conserving wide‐ranging species required countries with relatively strong governance to protect more land when they bordered nations with comparatively weak governance. Our results underscore the need for cross‐jurisdictional coordination and demonstrate how risk can be efficiently incorporated into conservation planning. Planeación de las áreas protegidas para conservar la biodiversidad en un futuro incierto

Misinformation, internet honey trading and beekeepers drive a plant invasion - Magdalena Lenda; Piotr Skórka; Karolina Kuszewska; Dawid Moroń; Michał Bełcik; Renata Baczek Kwinta; Franciszek Janowiak; David H. Duncan; Peter A. Vesk; Hugh P. Possingham; Johannes M. H. Knops (Ecology Letters, 2021)
Biological invasions are a major human induced global change that is threatening global biodiversity by homogenizing the world’s fauna and flora. Species spread because humans have moved species across geographical boundaries and have changed ecological factors that structure ecosystems, such as nitrogen deposition, disturbance, etc. Many biological invasions are caused accidentally, as a byproduct of human travel and commerce driven product shipping. However, humans also have spread many species intentionally because of perceived benefits. Of interest is the role of the recent exponential growth in information exchange via internet social media in driving biological invasions. To date, this has not been examined. Here, we show that for one such invasive species, goldenrod, social networks spread misleading and incomplete information that is enhancing the spread of goldenrod invasions into new environments. We show that the notion of goldenrod honey as a “superfood” with unsupported healing properties is driving a demand that leads beekeepers to produce goldenrod honey. Social networks provide a forum for such information exchange and this is leading to further spread of goldenrod in many countries where goldenrod is not native, such as Poland. However, this informal social information exchange ignores laws that focus on preventing the further spread of invasive species and the strong negative effects that goldenrod has on native ecosystems, including floral resources that negatively impact honeybee performance. Thus, scientifically unsupported information on “superfoods” such as goldenrod honey that is disseminated through social internet networks has real world consequences such as increased goldenrod invasions into novel geographical regions which decreases native biodiversity.

Metrics of progress in the understanding and management of threats to Australian birds - S. T. Garnett; S. H. M. Butchart; G. B. Baker; E. Bayraktarov; K. L. Buchanan; A. A. Burbidge; A. L. M. Chauvenet; L. Christidis; G. Ehmke; M. Grace; D. G. Hoccom; S. M. Legge; et al. (Conservation Biology, 2019)
Although evidence‐based approaches have become commonplace for determining the success of conservation measures for the management of threatened taxa, there are no standard metrics for assessing progress in research or management. We developed 5 metrics to meet this need for threatened taxa and to quantify the need for further action and effective alleviation of threats. These metrics (research need, research achievement, management need, management achievement, and percent threat reduction) can be aggregated to examine trends for an individual taxon or for threats across multiple taxa. We tested the utility of these metrics by applying them to Australian threatened birds, which appears to be the first time that progress in research and management of threats has been assessed for all threatened taxa in a faunal group at a continental scale. Some research has been conducted on nearly three‐quarters of known threats to taxa, and there is a clear understanding of how to alleviate nearly half of the threats with the highest impact. Some management has been attempted on nearly half the threats. Management outcomes ranged from successful trials to complete mitigation of the threat, including for one‐third of high‐impact threats. Progress in both research and management tended to be greater for taxa that were monitored or occurred on oceanic islands. Predation by cats had the highest potential threat score. However, there has been some success reducing the impact of cat predation, so climate change (particularly drought), now poses the greatest threat to Australian threatened birds. Our results demonstrate the potential for the proposed metrics to encapsulate the major trends in research and management of both threats and threatened taxa and provide a basis for international comparisons of evidence‐based conservation science.

Reach and messages of the world's largest ivory burn - Alexander Braczkowski; Matthew H. Holden; Christopher O'Bryan; Chi‐Yeung Choi; Xiaojing Gan; Nicholas Beesley; Yufang Gao; James Allan; Peter Tyrrell; Daniel Stiles; Peadar Brehony; Revocatus Meney; et al. (Conservation Biology, 2018)
Recent increases in ivory poaching have depressed African elephant populations. Successful enforcement has led to ivory stockpiling. Stockpile destruction is becoming increasingly popular, and most destruction has occurred in the last 5 years. Ivory destruction is intended to send a strong message against ivory consumption, both in promoting a taboo on ivory use and catalyzing policy change. However, there has been no effort to establish the distribution and extent of media reporting on ivory destruction events globally. We analyzed media coverage of the largest ivory destruction event in history (Kenya, 30 April 2016) across 11 nation states connected to ivory trade. We used an online‐media crawling tool to search online media outlets and subjected 5 of the largest print newspapers (by circulation) in 5 nations of interest to content analysis. Most online news on the ivory burn came from the United States (81% of 1944 articles), whereas most of the print news articles came from Kenya (61% of 157 articles). Eighty‐six to 97% of all online articles reported the burn as a positive conservation action, whereas 4–50% discussed ivory burning as having a negative impact on elephant conservation. Most articles discussed law enforcement and trade bans as effective for elephant conservation. There was more relative search interest globally in the 2016 Kenyan ivory burn than any other burn in 5 years. Ours is the first attempt to track the reach of media coverage relative to an ivory burn and provides a case study in tracking the effects of a conservation‐marketing event.

Revisiting “Success” and “Failure” of Marine Protected Areas: A Conservation Scientist Perspective - Sylvaine Giakoumi; Jennifer McGowan; Morena Mills; Maria Beger; Rodrigo H. Bustamante; Anthony Charles; Patrick Christie; Matthew Fox; Pablo Garcia-Borboroglu; Stefan Gelcich; Paolo Guidetti; Peter Mackelworth; et al. (Frontiers in Marine Science, 2018)

Correction to: Ocean zoning within a sparing versus sharing framework - Jennifer McGowan; Michael Bode; Matthew H. Holden; Katrina Davis; Nils C. Krueck; Maria Beger; Katherine L. Yates; Hugh P. Possingham (Theoretical Ecology, 2018)

Ocean zoning within a sparing versus sharing framework - Jennifer McGowan; Michael Bode; Matthew H. Holden; Katrina Davis; Nils C. Krueck; Maria Beger; Katherine L. Yates; Hugh P. Possingham (Theoretical Ecology, 2018)

Controlling range expansion in habitat networks by adaptively targeting source populations - Karlo Hock; Nicholas H. Wolff; Roger Beeden; Jessica Hoey; Scott A. Condie; Kenneth R. N. Anthony; Hugh P. Possingham; Peter J. Mumby (Conservation Biology, 2016)
Controlling the spread of invasive species, pests, and pathogens is often logistically limited to interventions that target specific locations at specific periods. However, in complex, highly connected systems, such as marine environments connected by ocean currents, populations spread dynamically in both space and time via transient connectivity links. This results in nondeterministic future distributions of species in which local populations emerge dynamically and concurrently over a large area. The challenge, therefore, is to choose intervention locations that will maximize the effectiveness of the control efforts. We propose a novel method to manage dynamic species invasions and outbreaks that identifies the intervention locations most likely to curtail population expansion by selectively targeting local populations most likely to expand their future range. Critically, at any point during the development of the invasion or outbreak, the method identifies the local intervention that maximizes the long‐term benefit across the ecosystem by restricting species’ potential to spread. In so doing, the method adaptively selects the intervention targets under dynamically changing circumstances. To illustrate the effectiveness of the method we applied it to controlling the spread of crown‐of‐thorns starfish ( Acanthaster sp.) outbreaks across Australia's Great Barrier Reef. Application of our method resulted in an 18‐fold relative improvement in management outcomes compared with a random targeting of reefs in putative starfish control scenarios. Although we focused on applying the method to reducing the spread of an unwanted species, it can also be used to facilitate the spread of desirable species through connectivity networks. For example, the method could be used to select those fragments of habitat most likely to rebuild a population if they were sufficiently well protected.

Continental‐Scale Governance and the Hastening of Loss of Australia's Biodiversity - Euan G. Ritchie; Corey J. A. Bradshaw; Chris R. Dickman; Richard Hobbs; Christopher N. Johnson; Emma L. Johnston; William F. Laurance; David Lindenmayer; Michael A. McCarthy; Dale G. Nimmo; Hugh H. Possingham; Robert L. Pressey; et al. (Conservation Biology, 2013)

Effects of climate‐driven primary production change on marine food webs: implications for fisheries and conservation - C. J. BROWN; E. A. FULTON; A. J. HOBDAY; R. J. MATEAR; H. P. POSSINGHAM; C. BULMAN; V. CHRISTENSEN; R. E. FORREST; P. C. GEHRKE; N. A. GRIBBLE; S. P. GRIFFITHS; H. LOZANO‐MONTES; et al. (Global Change Biology, 2010)
Climate change is altering the rate and distribution of primary production in the world's oceans. Primary production is critical to maintaining biodiversity and supporting fishery catches, but predicting the response of populations to primary production change is complicated by predation and competition interactions. We simulated the effects of change in primary production on diverse marine ecosystems across a wide latitudinal range in Australia using the marine food web model Ecosim. We link models of primary production of lower trophic levels (phytoplankton and benthic producers) under climate change with Ecosim to predict changes in fishery catch, fishery value, biomass of animals of conservation interest, and indicators of community composition. Under a plausible climate change scenario, primary production will increase around Australia and generally this benefits fisheries catch and value and leads to increased biomass of threatened marine animals such as turtles and sharks. However, community composition is not strongly affected. Sensitivity analyses indicate overall positive linear responses of functional groups to primary production change. Responses are robust to the ecosystem type and the complexity of the model used. However, model formulations with more complex predation and competition interactions can reverse the expected responses for some species, resulting in catch declines for some fished species and localized declines of turtle and marine mammal populations under primary productivity increases. We conclude that climate‐driven primary production change needs to be considered by marine ecosystem managers and more specifically, that production increases can simultaneously benefit fisheries and conservation. Greater focus on incorporating predation and competition interactions into models will significantly improve the ability to identify species and industries most at risk from climate change.

Major Conservation Policy Issues for Biodiversity in Oceania - R. T. KINGSFORD; J. E. M. WATSON; C. J. LUNDQUIST; O. VENTER; L. HUGHES; E. L. JOHNSTON; J. ATHERTON; M. GAWEL; D. A. KEITH; B. G. MACKEY; C. MORLEY; H. P. POSSINGHAM; et al. (Conservation Biology, 2009)
Oceania is a diverse region encompassing Australia, Melanesia, Micronesia, New Zealand, and Polynesia, and it contains six of the world's 39 hotspots of diversity. It has a poor record for extinctions, particularly for birds on islands and mammals. Major causes include habitat loss and degradation, invasive species, and overexploitation. We identified six major threatening processes (habitat loss and degradation, invasive species, climate change, overexploitation, pollution, and disease) based on a comprehensive review of the literature and for each developed a set of conservation policies. Many policies reflect the urgent need to deal with the effects of burgeoning human populations (expected to increase significantly in the region) on biodiversity. There is considerable difference in resources for conservation, including people and available scientific information, which are heavily biased toward more developed countries in Oceania. Most scientific publications analyzed for four threats (habitat loss, invasive species, overexploitation, and pollution) are from developed countries: 88.6% of Web of Science publications were from Australia (53.7%), New Zealand (24.3%), and Hawaiian Islands (10.5%). Many island states have limited resources or expertise. Even countries that do (e.g., Australia, New Zealand) have ongoing and emerging significant challenges, particularly with the interactive effects of climate change. Oceania will require the implementation of effective policies for conservation if the region's poor record on extinctions is not to continue .

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

The influence of multiple dispersal mechanisms and landscape structure on population clustering and connectivity in fragmented artesian spring snail populations - J. WORTHINGTON WILMER; C. ELKIN; C. WILCOX; L. MURRAY; D. NIEJALKE; H. POSSINGHAM (Molecular Ecology, 2008)
Many organisms occupy heterogeneous landscapes that contain both barriers to movement as well as corridors that facilitate dispersal. The extent to which such features determine population connectivity will depend on the mechanisms utilized by organisms to disperse. Here we examined the interaction between landscape structure and dispersal in the endemic aquatic snail, Fonscochlea accepta , in the fragmented artesian spring ecosystem of arid central Australia. We used frequentist and Bayesian analyses of microsatellite data to identify population structure and immigration for 1130 snails sampled from 50 springs across an entire spring complex. We introduce a modified isolation‐by‐distance analysis to test hypotheses about how populations are clustered and to distinguish the most likely dispersal pathways within and between those clusters. Highly significant differences in F ST values and significant isolation‐by‐distance patterns were detected among springs across the entire complex, while Bayesian assignment tests revealed the presence of two hierarchical levels of spring clustering. Clusters were defined by the spatial aggregation of springs, dynamic aquatic habitat connections between springs and the ecology of the snails. Bayesian immigrant identification and our modified isolation‐by‐distance analysis revealed that dispersal occurs at two geographical scales via two very different mechanisms. Short range dispersal (usually ≤ 300 m) occurs via active movement facilitated by aquatic connections among springs while long‐range dispersal (≥ 3 km) is likely facilitated by an animal vector (phoresy). These results underline the importance of both dispersal mode and landscape structure in influencing connectivity rates and patterns among populations.

Conservation planning with irreplaceability: does the method matter? - J. Carwardine; W. A. Rochester; K. S. Richardson; K. J. Williams; R. L. Pressey; H. P. Possingham (Biodiversity and Conservation, 2007)

How accurate are population models? Lessons from landscape‐scale tests in a fragmented system - D. B. Lindenmayer; H. P. Possingham; R. C. Lacy; M. A. McCarthy; M. L. Pope (Ecology Letters, 2003)
There is a growing debate about the ability of Population Viability Analysis (PVA) to predict the risk of extinction. Previously, the debate has focused largely on models where spatial variation and species movement are ignored. We present a synthesis of the key results for an array of different species for which detailed tests of the accuracy of PVA models were completed. These models included spatial variation in habitat quality and the movement of individuals across a landscape. The models were good approximations for some species, but poor for others. Predictive ability was limited by complex processes typically overlooked in spatial population models, these being interactions between landscape structure and life history attributes. Accuracy of models could not be determined a priori, although model tests indicated how they might be improved. Importantly, model predictions were poor for some species that are among the best‐studied vertebrates in Australia. This indicated that although the availability of good life history data is a key part of PVA other factors also influence model accuracy. We were also able to draw broad conclusions about the sorts of populations and life history characteristics where model predictions are likely to be less accurate. Predictions of extinction risk are often essential for real‐world population management. Therefore, we believe that although PVA has been shown to be less than perfect, it remains a useful tool particularly in the absence of alternative approaches. Hence, tests of PVA models should be motivated by the cycle of testing and improvement.

The Focal‐Species Approach and Landscape Restoration: a Critique - D. B. Lindenmayer; A. D. Manning; P. L. Smith; H. P. Possingham; J. Fischer; I. Oliver; M. A. McCarthy (Conservation Biology, 2002)
In many parts of the world there is an urgent need for landscape restoration to conserve biodiversity. Landscape restoration is not straightforward, however, because many issues and processes must be understood for effective action to take place. In an attempt to guide restoration efforts for biodiversity conservation, developed a taxon‐based surrogate scheme called the focal‐species approach. The focal‐species approach involves the identification of a suite of species targeted for the management of threatening processes and vegetation‐restoration efforts. Together, their “requirements for persistence define the attributes that must be present if [the landscape] is to meet the needs of the remaining biota” ( ). Some of our concerns with the focal‐species approach include the following. First, the underlying theoretical basis of the focal‐species approach is problematic. As part of a taxon‐based surrogate scheme, a suite of focal species is presumed to act collectively as a surrogate for other elements of the biota. But taxon‐based surrogate schemes have had limited success everywhere they have been applied. Second, the focal‐species approach may be unsuitable for practical implementation, primarily because of the lack of data to guide the selection of a set of focal species in the majority of landscapes. We argue that restoration strategies should be based on appropriate theory, realistic assessment of available information, and an achievable outcome for the land managers who own or control the majority of land in the most significantly affected landscapes. Given the potential limitations of the focal‐species approach, a mix of different strategies should be adopted in any given landscape and between different landscapes to spread risk of failure of any one approach. We believe that it is important to raise awareness about the potential limitations of the focal‐species approach and to ensure that land managers do not assume it will inevitably lead to the conservation of all biota in a landscape.

Testing the Accuracy of Population Viability Analysis - M. A. McCarthy; H. P. Possingham; J. R. Day; A. J. Tyre (Conservation Biology, 2001)
Despite the growing use of population viability analysis ( PVA), the predictions of these models rarely have been tested with field data that were not used in initially developing the model. We review and discuss a suite of methods that may be used to test the predictive ability of models used in PVA. In addition to testing mean predictions, appropriate methods must analyze the probability distribution of the model predictions. The methods we discuss provide tests of the mean predictions, the predicted frequency of events such as extinction and colonization, and the predicted probability distribution of state variables. We discuss visual approaches based on plots of observations versus the predictions and statistical approaches based on determining significant differences between observations and predictions. The advantages and disadvantages of each method are identified. The best methods test the statistical distribution of the predictions; those that ignore variability are meaningless. Although we recognize that the quality of a model is not solely a function of its predictive abilities, tests help reduce inherent model uncertainty. The role of model testing is not to prove the truth of a model, which is impossible because models are never a perfect description of reality. Rather, testing should help identify the weakest aspects of models so they can be improved. We provide a framework for using model testing to improve the predictive performance of PVA models, through an iterative process of model development, testing, subsequent modification and re‐testing.

Effects of data characteristics on the results of reserve selection algorithms - R. L. Pressey; H. P. Possingham; V. S. Logan; J. R. Day; P. H. Williams (Journal of Biogeography, 1999)
Summary We tested the effects of four data characteristics on the results of reserve selection algorithms. The data characteristics were nestedness of features (land types in this case), rarity of features, size variation of sites (potential reserves) and size of data sets (numbers of sites and features). We manipulated data sets to produce three levels, with replication, of each of these data characteristics while holding the other three characteristics constant. We then used an optimizing algorithm and three heuristic algorithms to select sites to solve several reservation problems. We measured efficiency as the number or total area of selected sites, indicating the relative cost of a reserve system. Higher nestedness increased the efficiency of all algorithms (reduced the total cost of new reserves). Higher rarity reduced the efficiency of all algorithms (increased the total cost of new reserves). More variation in site size increased the efficiency of all algorithms expressed in terms of total area of selected sites. We measured the suboptimality of heuristic algorithms as the percentage increase of their results over optimal (minimum possible) results. Suboptimality is a measure of the reliability of heuristics as indicative costing analyses. Higher rarity reduced the suboptimality of heuristics (increased their reliability) and there is some evidence that more size variation did the same for the total area of selected sites. We discuss the implications of these results for the use of reserve selection algorithms as indicative and real‐world planning tools.